POLA KOMUNIKASI GURU DAN ANAK DIDIK DALAM PEMBELAJARAN AKUNTANSI DI KELAS XII SMA ISLAMIYAH PONTIANAK - Kiky Afrianti; Maria Ulfah; Witarsa Witarsa (Universitas Tanjungpura, 2019)
AbstractThis study aimed to find out how the communication patterns of teachers and students in accounting learning in class XII Pontianak Islamic High School. The form of this research was qualitative research with a type of case study research. Data was collected by observation and interview. The data analysis technique used was data education, display data and drawing conclusions and verification. The results of this study indicated that communication patterns as actions and communication as interactions often occur in teaching and learning activities because teachers often use the lecture method at the beginning of learning and communication as an interaction when explaining the material. Communication patterns of teacher-student-students, teacher-student communication patterns, student-teacher children, students / students / communication as student transactions, circular communication patterns were categorized as rare in the accounting learning process due to frequent communication patterns happens namely the pattern of communication as action and communication as interaction. Communication patterns that occur in teaching and learning activities in class XII Islamiyah changed comtinously. Keywords: accountance, communication patterns ofteachers and students